Migration and social upheaval in the face of globalization in Central Asia - Laruelle, Marlène (Social sciences in Asia, 2013)
Since the start of the 1990s, Central Asia has been the main purveyor of migrants in the post-Soviet space. These massive migrations impact issues of governance; patterns of social adaptation; individual and collective identity transformations; and gender relation in Central Asia.